Laurence -Moon-Bardet- Biedl syndrome with Diabetes Mellitus (Journal of Medicine, 2012)
A 13 year old boy presented with obesity, reduced vision, mental retardation, hypogonadism, delayed development and learning difficulty. On examination, he had polydactyly, moon face, bilateral gynaecomastia, small penis and testis. Retinitis pigmentosa was found on fundoscopy. With these typical features, he was diagnosed as a case of Laurence-Moon-Bardet-Beidle syndrome. It is a rare autosomal recessive disorder with mutation in 6 loci identified so far. It is commonly found in communities with high inter-family marriage. Clinical features appear early in childhood and diagnosis is usually done by puberty. Prominent features include rod-cone dystrophy leading to blindness, postaxial polydactyly, central obesity, learning disability, hypogonadism in males, renal dysfunction with increased risk for renal cell carcinoma. DOI: http://dx.doi.org/10.3329/jom.v13i1.10083 JOM 2012; 13(1): 97-99